Wernicke encephalopathy: a mini review of the clinical spectrum, atypical manifestations, and diagnostic challenges - Siping Li; Chengzhi Xing (Frontiers in Neurology, 2025)
BackgroundWernicke encephalopathy (WE) is a severe neurological disorder caused by thiamine (vitamin B1) deficiency. Though often associated with chronic alcohol abuse, it can also arise from other conditions that impair thiamine intake or absorption. The classic triad of symptoms includes ophthalmoplegia, an abnormal mental state, and gait ataxia, although these may not be present in all patients, leading to underdiagnosis and undertreatment.MethodsThis mini review synthesizes data from clinical studies, autopsy reports, and imaging findings to assess the prevalence, diagnostic challenges, and treatment protocols for WE. It examines the role of various etiological factors, the presentation of atypical symptoms, and the utility of diagnostic tools such as magnetic resonance imaging (MRI) and vitamin B1 assays.ResultsAutopsy studies report a prevalence of WE that ranges from 0.4 to 2.8%, with most patients experiencing alcohol addiction or having other alcohol use disorders. The diagnosis of WE is primarily clinical, based on the Caine criteria in which a person must display at least two of the three classic symptoms or evidence of nutritional deficiency. MRI is a valuable tool for diagnosing WE, typically showing symmetric T2/FLAIR hyperintense signals in specific brain regions. Treatment involves prompt thiamine replacement, with intravenous administration being the most effective method to ensure adequate brain uptake.ConclusionWE remains a challenging condition to diagnose due to its variable presentations and the potential for atypical symptoms. Early recognition and treatment with thiamine are crucial to prevent irreversible neurological damage or death. There is a need for clear diagnostic and treatment guidelines to improve the management of WE and reduce the risk of underdiagnosis and undertreatment.